2019
DOI: 10.1002/jcb.29267
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of long noncoding TNFSF10 contributes to osteoarthritis progression through the miR‐376‐3p/FGFR1 axis

Abstract: Osteoarthritis (OA) is a common joint disease with high morbidity, but there is still no definitive treatment for it. Long noncoding RNAs (lncRNAs) have been confirmed to play key roles in OA progression. This work was done to investigate the roles and action mechanism of lncRNA TNFSF10 in OA. The messenger RNA levels of TNFSF10 in articular cartilage samples from patients or chondrocytes were detected by Quantitative real-time PCR assay (qRT-PCR).The effects of TNFSF10 on chondrocytes were evaluated on the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 37 publications
0
14
1
Order By: Relevance
“…found that lncRNA XIST in cartilage samples in patients with OA was significantly upregulated, and XIST served as a ceRNA for miR‐211 to counteract miR‐211‐mediated CXCR4 repression, thereby modulating chondrocyte proliferation and apoptosis through downstream MAPK signaling. In another study, Huang et al . found that lncRNA TNFSF10 was upregulated in OA cartilages and stimulated cell proliferation, antiapoptosis, and inflammation for chondrocytes.…”
Section: Discussionmentioning
confidence: 97%
“…found that lncRNA XIST in cartilage samples in patients with OA was significantly upregulated, and XIST served as a ceRNA for miR‐211 to counteract miR‐211‐mediated CXCR4 repression, thereby modulating chondrocyte proliferation and apoptosis through downstream MAPK signaling. In another study, Huang et al . found that lncRNA TNFSF10 was upregulated in OA cartilages and stimulated cell proliferation, antiapoptosis, and inflammation for chondrocytes.…”
Section: Discussionmentioning
confidence: 97%
“…Previous study has suggested SMAD7 can induce growth and inhibit apoptosis in colon adenocarcinoma cells and acts as a tumor promoter [35], indicating that miR-581-mediated apoptosis might be SMAD7/TGFβ-pathway-independent. Moreover, in the results of miR-581 target genes, TNFSF10 [36,37], HMGA2 [38], CEACAM1 [39,40], and mTOR [41] have been reported to be involved in proliferation and apoptosis in a number of cancers. There is a strong possibility that miR-581 regulates CRC proliferation and apoptosis by targeting these genes.…”
Section: Discussionmentioning
confidence: 99%
“…From inflammatory responses in diabetic nephropathy [ 156 ] and vascular endothelial cells (VECs) [ 157 ] to the regulation of osteoarthritis progression [ 158 , 159 ] or in periodontitis [ 160 , 161 ], many biological processes are found involved in the class of inflammatory mechanisms.…”
Section: Cerna and Diseasesmentioning
confidence: 99%